THE DEVELOPMENT OF ONLINE TEACHING AND LEARNING OF CHINESE CALLIGRAPHY - Saengsi, Atchara (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2025)
The purposes of this study were to: 1) compare the learning outcomes of online Chinese character calligraphy writing before and after the course for the first-year students in the Chinese Business program; 2) compare the pre-study and post-study attitudes of the first-year students in Business Chinese program towards online teaching of Chinese calligraphy writing, and 3) develop online Chinese calligraphy writing course management. The research design is a mixed-methods approach. That is, collecting both quantitative and qualitative data. The sample group consisted of 48 first-year students in Business Chinese program from the Faculty of Humanities and Social Sciences, Phranakhon Rajabhat University. The tool used to collect data was a Google Form test, divided into 2 parts: 1) a test before and after online Chinese calligraphy writing learning and 2) an attitude test before and after online Chinese calligraphy writing learning. The quantitative data analysis method involved calculating percentages, means, and standard deviations, and qualitative data analysis using Content Analysis. The research found that the results of the comparison between the online Chinese calligraphy writing achievement before and after the course for the first-year students in the Chinese Business program is of 42.40% / 70.36 % with the means of 4.29 / 4.44 ( = 4.29 / 4.44) and the standard deviation of 0.39 / 0.16 (S.D. = 0.39 / 0.16). As for the results of comparing attitudes before and after online Chinese calligraphy writing course in 3 areas: including mental and cognitive aspects, teaching and learning activities and online learning. The total percentage is of 85.77 / 88.95 (85.77% / 88.95%), the mean is 4.29 / 4.44 ( = 4.29 / 4.44), and the standard deviation is 0.39 / 0.16 (S.D. = 0.39 / 0.16). It shows that students' attitudes after learning Chinese calligraphy writing are significantly higher than before learning. Factors affecting positive results include emphasizing letters as the main focus, teaching the parts of the alphabet proper description of characters, including the use of various technologies to increase interest and create a good attitude in learning